Pemberdayaan Umkm Gerabah Kesilir Melalui Pembentukan Komunitas Pra Koperasi - Eva Tyas Utami; Rike Oktarianti; Dwi Setyati; Anik Swandari (SULUH: Jurnal Abdimas, 2025)
The creative industry is an economic sector that does not require a large scale of production. One of the creative industries that is developing in Demangan Babatan, Kesilir Village, Wuluhan District, Jember Regency is the pottery industry with raw materials made of clay. There are quite a number of pottery products with quite varied designs. However, there are still problems faced by pottery craftsmen in the area, namely the lack of capital, marketing networks and the absence of regeneration in this business. To overcome these problems, it is necessary to provide training and the formation of pre-cooperatives for craftsmen. Service activities are carried out by forming a pre-cooperative community to facilitate the availability of capital for craftsmen.